2015
DOI: 10.1177/2156869315570480
|View full text |Cite
|
Sign up to set email alerts
|

Flourishing

Abstract: Positive mental health (PMH) is an important construct for understanding the full continuum of mental health. Some socially disadvantaged populations experience a paradoxically high level of PMH despite negative social experiences including discrimination. The purpose of this study is to examine the prevalence and culturally salient correlates of PMH among a cross-sectional sample of 218 American Indian adults living with type 2 diabetes mellitus. Although 17.1 percent of individuals in this sample met Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…For example, participation in traditional spiritual activities has been found to be associated with a lower likelihood of past-year alcohol abuse (Whitbeck et al 2004), and low enculturation has been found to be a strong predictor of alcohol problems (Currie et al 2011). Culture has been shown to be connected to positive mental health (Kading et al 2015), positive psychological well-being (Moran et al 1999), resiliency factors among adolescents such as positive attitude toward schools and reaching academic goals (LaFromboise et al 2006), greater happiness, and the use of religion or spirituality (versus substances) to cope with stress (Wolsko et al 2007). Health benefits of culture and spirituality have always been understood by tribal communities and often requested within treatment programs (Legha and Novins 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, participation in traditional spiritual activities has been found to be associated with a lower likelihood of past-year alcohol abuse (Whitbeck et al 2004), and low enculturation has been found to be a strong predictor of alcohol problems (Currie et al 2011). Culture has been shown to be connected to positive mental health (Kading et al 2015), positive psychological well-being (Moran et al 1999), resiliency factors among adolescents such as positive attitude toward schools and reaching academic goals (LaFromboise et al 2006), greater happiness, and the use of religion or spirituality (versus substances) to cope with stress (Wolsko et al 2007). Health benefits of culture and spirituality have always been understood by tribal communities and often requested within treatment programs (Legha and Novins 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ideas of community well-being and health can be much different than the dominant culture, and researchers should consider finding new ways to measure positive health variables. For example, while American Indians have disproportionately higher rates of depression when compared to national averages, over half (51.5%) of one study population also experienced flourishing positive mental health (Kading et al 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, quantitative evidence for the buffering influence of cultural identity on health and problem behaviours is unclear (Walls, Whitbeck, & Armenta, 2016). However, other investigations have produced contrasting findings (Kading et al, 2015;Paradies & Cunningham, 2012). However, other investigations have produced contrasting findings (Kading et al, 2015;Paradies & Cunningham, 2012).…”
mentioning
confidence: 99%
“…Department of Health and Human Services, 2012) and display disproportionately high rates and earlier onset of certain psychiatric disorders (Whitbeck, Hoyt, Johnson, & Chen, 2006; Whitbeck, Sittner Hartshorn, Crawford, Walls, Gentzler, & Hoyt, 2014; Beals, Novins, Whitesell, Mitchell, & Manson, 2005). While such disparities have very real public health impacts worthy of our attention, also critical to understanding Indigenous health is evidence of resilience, positive mental health, and abstinence from substance use (Kading, et al, 2015; Substance Abuse and Mental Health Services Administration [SAMHSA], 2014). In addition, socio-cultural contexts likely drive important differences in mental health trends and correlates across diverse tribal groups (e.g., Indian Health Service [HIS], 2008; Novins, et al, 1999).…”
mentioning
confidence: 99%